Nature, Reimagined - Çibik, Naz Fulya; Çam, Aylin (Journal of Interdisciplinary Studies in Education, 2026)
Adults influence younger generations and play an important role in responding to climate change. This qualitative case study explored the impact of a 12-week Online Nature Workshop (ONW) program, consisting of six biweekly sessions, focused on adults’ perceptions and experiences of nature. Workshops addressed themes such as human-nature relationships, ecological footprints, composting, biodiversity, and slow living, through hands-on activities that could be done at home. Ten adults (aged 18-31) engaged in interactive, experiential activities delivered online. Data were collected with open-ended pre-post questionnaires and nature diaries. The study showed that before the ONWs, participants described nature only in terms of human benefit, but afterward, they began to see it as an interconnected system where humans co-exist with other living beings.